Evaluation of the Effect of Sports Activities on Syrian Students' Social Cohesion Within the Scope of School Social Work - Karakaya, Handan; Uzunaslan, Serif; Zirek, Oguzhan (Routledge Journals, Taylor & Francis Ltd, 2025)
The purpose of this study is to determine the effects of Syrian students under temporary protection in Turkey on social cohesion and personal development through their participation in sporting activities. The study, which was conducted with a descriptive phenomenological qualitative research design, included 36 Syrian students selected through purposive sampling. Data were collected through semi-structured in-depth interviews and analyzed thematically. As a result of the analysis, four main themes were identified: (a) support and participation in sport activities, (b) diversity of sport activities and motivation, (c) barriers to participation, and (d) the impact of sport activities on social cohesion and personal development. The findings suggest that sporting activities play an important role in migrant students' social integration and self-confidence. However, misunderstandings and perceptions of discrimination caused by language barriers and cultural differences can negatively affect participation in sports activities. It is emphasized that culturally sensitive supports in school social work play a critical role in this process.
Keywords: Sports; school social work; social cohesion; temporary protection